2021
DOI: 10.38043/jimb.v6i1.3060
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Inflasi, Suku Bunga, Dan Nilai Tukar Terhadap Indeks Harga Saham Gabungan Periode 2016 – 2018

Abstract: The movement of stock price index is the important indicator for investors to determine whether the investor would sell, buy, or hold shares. The movement of CSPI is affected by several factor like macroeconomy. The purpose of this study was to determine the effect of inflation, interest rate, and exchange rate against CSPI. Theoretically, the effect of inflation, interest rate, and exchange rate is based on efficient market hyphothesis and signalling theory which inflation, interest rate and exchange rate pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 1 publication
0
7
0
5
Order By: Relevance
“…Total net worth can be calculated from the NAV of the Mutual Fund. (Melyani, 2021) So it can be concluded that, NAV is the value of funds managed by investment managers for mutual funds in exchange trading which is recorded every day.…”
Section: Preliminarymentioning
confidence: 99%
“…Total net worth can be calculated from the NAV of the Mutual Fund. (Melyani, 2021) So it can be concluded that, NAV is the value of funds managed by investment managers for mutual funds in exchange trading which is recorded every day.…”
Section: Preliminarymentioning
confidence: 99%
“…Enflasyon nedeniyle mal ve hizmet fiyatlarının artması satın alma gücünü azaltarak ulusal para hakimiyetinin kaybolmasına neden olabilir. Enflasyonun yükselmesi ekonomide gerilemeyi tetikleyerek şirket kârlılıklarının azalmasına ve pay senedi fiyatlarının daha az rekabetçi olmasına neden olacaktır (Flannery ve Protopapadakis, 2002;Fahlevi, 2019: 158;Melyani, 2021). Riskten kaçınma amacı içinde olan yatırımcılar bu durumda enflasyon belirsizliği ile karşı karşıya kalabilirler.…”
Section: Introductionunclassified
“…56% of the use of industrial materials is from silver worldwide, not comparable to the use of gold for industry which is only used about 12%. According to article from (Melyani, 2021)the price of silver jumped 7.4% in the Spot market with a value of US$28.98 per ounce. Throughout 2021, oil prices have increased drastically.…”
Section: Introductionmentioning
confidence: 99%